The architecture of cultural enterprise: a study of design reflexivity in action - Greenman, Andrew (2008)
The cultural industries have an increasingly important role to play in policies addressing the UK's present and future economic competitiveness. Researching how entrepreneurial activity leads to the creation and maintenance of cultural enterprises is central to understanding the value added by such organisations. The present research contributes to our understanding of these important issues. An ethnographic approach, which is defined here as a set of methods for conducting field work (e.g., participant observation and semi-structured interviews) and a methodology for textual representations of social activity, is adopted to explore design thinking in action.